Penerapan Model Kooperatif Tipe Peer Teaching untuk Meningkatkan Hasil Belajar Matematika Siswa Sekolah Dasar - Walewangko, Stief Aristo; Kasiahe, Evi Martika; Lomban, Edino Ayub; Muhonis, Dina (FAKULTAS AGAMA ISLAM UNIVERSITAS BILLFATH, 2023)
This research examined the application of the peer teaching type cooperative model to improve mathematics learning outcomes of grade IVa students at 03 Manado Public Elementary School. This research was classroom action research (CAR) with two cycles. Data were collected through observation, tests, interviews, and documentation. Observations were used to observe the teacher and students’ activities each cycle. Tests were used to measure students' learning outcomes after using the peer teaching-learning model. Interviews were used to obtain opinions and an overview of the application of the peer teaching model. Documentation was used to describe events in the classroom during learning. The results showed that the application of peer teaching-learning method succeeded in improving the mathematics learning outcomes of grade Iva students at 03 Manado Public Elementary School, which was 41.93% in cycle I and 74.19% in cycle II. Based on the data analysis, it can be concluded that mathematics learning using peer teaching method was effective in increasing the students’ learning outcome on stacked multiplication subjects.